Mitigating void growth in out-of-autoclave prepreg processing using a semi-permeable membrane to maintain resin pressure - Daniel Zebrine; Mark Anders; Steven Nutt (Advanced Manufacturing: Polymer & Composites Science, 2022)
AbstractIn this work, we investigate the use of discontinuous resin films in prepregs (semipregs) combined with a semi-permeable (air-permeable, resin-impermeable) release film intended to allow through-thickness air evacuation while simultaneously restricting resin loss. In situ measurements of resin pressure were deployed to test the hypothesis that resin pressure was maintained during prepreg cure when using a semi-permeable release film. Concurrently, visualization of the tool-side surface during cure revealed efficient evacuation of entrapped air. Porosity in laminates formed at high temperatures when using resin-permeable consumables, but did not form when using resin-impermeable (semi-permeable) consumables. To confirm that the observed void growth behavior was due to a loss in resin pressure, experiments were conducted to measure resin pressure during cure with both resin-permeable and resin-impermeable (semi-permeable) consumables. In both cases, resin pressure peaked before decreasing, a finding attributed to resin flowing to fill dry regions in the fabric, present by design. The drop in resin pressure, however, was greater in magnitude and longer in duration when using resin-permeable edge and bag-side surface boundaries, indicating that the observed void growth at elevated temperature was caused by a loss in resin pressure. Use of a semi-permeable membrane was effective in retaining resin content and mitigating such porosity.